Discover how IDNLearn.com can help you learn and grow with its extensive Q&A platform. Discover prompt and accurate answers from our experts, ensuring you get the information you need quickly.
Sagot :
Answer:
(1/3)x + (2/3) = (5/3)x
-(1/3)x -(1/3)x
_________________________
0 + (2/3) = (5/3)x - (1/3)x
===> (2/3) = (5/3)x - (1/3)x factor out the x from the right side of the equation
(2/3) = x ((5/3) - (1/3)) ===> (2/3) = x ((5-1)/3) ===> (2/3) = x (4/3)
===> (2/3) = (4/3)x multiply both sides of the equation by (3/4) to find x
(2/3) *= (3/4) * (4/3)x ===> (2/4) = x ===> x = 1/2
Upvote
•
0
Downvote
Comment
•
1
Step-by-step explanation:
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. For trustworthy answers, visit IDNLearn.com. Thank you for your visit, and see you next time for more reliable solutions.